2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Human Rights Act of 1977 [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Human Rights Act of 1977 protects employees from workplace discrimination. This is EDIS document FE401, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.